2021
DOI: 10.3390/jmse9090971
|View full text |Cite
|
Sign up to set email alerts
|

Standardising Marine Renewable Energy Testing: Gap Analysis and Recommendations for Development of Standards

Abstract: Marine renewable energy (MRE) is still an emerging technology. As such, there is still a lack of mature standards and guidance for the development and testing of these devices. The sector covers a wide range of disciplines, so there is a need for more comprehensive guidance to cover these. This paper builds on a study undertaken in the MaRINET2 project to summarise recommendations and guidance for testing MRE devices and components, by reviewing the recently published guidance. Perceived gaps in the guidance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The EU H2020 MaRINET2 project 2 aims to improve the quality, robustness and accuracy of physical modelling and testing practices implemented by test infrastructures. Research carried out within MaRINET2 [2,3] identified a shortfall in the published guidance available for laboratory testing of floating offshore wind turbines (FOWTs). Much of the existing literature is derived from the oil and gas industry and published by the ITTC in the 7.5-02-07-03 series that deals with ocean engineering 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EU H2020 MaRINET2 project 2 aims to improve the quality, robustness and accuracy of physical modelling and testing practices implemented by test infrastructures. Research carried out within MaRINET2 [2,3] identified a shortfall in the published guidance available for laboratory testing of floating offshore wind turbines (FOWTs). Much of the existing literature is derived from the oil and gas industry and published by the ITTC in the 7.5-02-07-03 series that deals with ocean engineering 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out within MaRINET2 [2,3] identified a shortfall in the published guidance available for laboratory testing of floating offshore wind turbines (FOWTs). Much of the existing literature is derived from the oil and gas industry and published by the ITTC in the 7.5-02-07-03 series that deals with ocean engineering 3 . The ITTC guidelines are relatively high level and do not provide standardised procedures for laboratory testing or detailed guidance on different aspects of FOWT testing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect that the facility used for the model tests will have on the outcomes is uncertain, even when following the same methodologies for carrying out the tests which is not often the case. Research carried out within MaRINET2 [2,3] identified a shortfall in the published guidance available for conducting laboratory testing of floating offshore wind turbines. Much of the existing literature is derived form the oil and gas industry and published by the International Towing Tank Conference (ITTC) literature that deals with ocean engineering 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out within MaRINET2 [2,3] identified a shortfall in the published guidance available for conducting laboratory testing of floating offshore wind turbines. Much of the existing literature is derived form the oil and gas industry and published by the International Towing Tank Conference (ITTC) literature that deals with ocean engineering 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental force measurements help provide confidence in system design and are a crucial requirement for a wide range of ocean and coastal engineering problems. For instance, force measurements are used to quantify structural loading on breakwaters [1][2][3], as well as loading on complex systems, such as remotely operated vehicles [4][5][6][7], offshore wind turbines [8][9][10][11], sediment transport and bottom fluvial erosion [12,13] and tidal stream turbines (TSTs) [14][15][16][17][18]. To obtain vector force measurements experimentally, force plates are typically used and are integrated into the structure and/or foundation.…”
Section: Introductionmentioning
confidence: 99%